New-Victorian Families: Gender, Sexual and Cultural Politics (Neo-Victorian Series, vol. 2) - Marie-luise Kohlke (Rodopi, 2011)
The second volume in Rodopi's Neo-Victorian Series, this collection considers the ways that neo-Victorian fictions of both normative and 'queer' families comment on the interrelationship between nineteenth-century and contemporary myths of individual, collective, and national identities based in the nuclear family as a source of economic, ideological, and cultural capital.